The effects of monetary policy in a small open economy : the case of Portugal - Sousa, Ricardo M. (2012)
In this paper, I analyze the macroeconomic effects of monetary policy on the Portuguese economy. I show that a positive interest rate shock leads to: (i) a contraction of real GDP and a substantial increase of the unemployment rate; (ii) a quick fall in the commodity price and a gradual decrease of the price level; and (iii) a downward correction of the stock price index. It also produces a "short-lived liquidity effect" and helps explaining the negative comovement between bonds and stocks. In addition, I find evidence suggesting the existence of a money demand function characterized by small output and interest rate elasticities. By its turn, the central bank´s policy rule follows closely the dynamics of the money markets. Finally, both the real GDP and the price level in Portugal would have been higher during almost the entire sample period if there were no monetary policy surprises.